Peritoneal Dialysis Tailored to Pediatric Needs. (8th June 2011) - Schmitt, C. P.; Zaloszyc, A.; Schaefer, B.; Fischbach, M.
Abstract : Consideration of specific pediatric aspects is essential to achieve adequate peritoneal dialysis (PD) treatment in children. These are first of all the rapid growth, in particular during infancy and puberty, which must be accompanied by a positive calcium balance, and the age dependent changes in body composition. The high total body water content and the high ultrafiltration rates required in anuric infants for adequate nutrition predispose to overshooting convective sodium losses and severe hypotension. Tissue fragility and rapid increases in intraabdominal fat mass predispose to hernia and dialysate leaks. Peritoneal equilibration tests should repeatedly been performed to optimize individual dwell time. Intraperitoneal pressure measurements give an objective measure of intraperitoneal filling, which allow for an optimized dwell volume, that is, increased dialysis efficiency without increasing the risk of hernias, leaks, and retrofiltration. We present the concept of adapted PD, that is, the combination of short dwells with low fill volume to promote ultrafiltration and long dwells with a high fill volume to improve purification within one PD session. The use of PD solutions with low glucose degradation product content is recommended in children, but unfortunately still not feasible in many countries.